Testing the Influence of Corporate Board diversity, Board Composition, and Board CSR Awareness on Environment Sustainable Disclosure? - Evidence from Chinese Information Technology Services Industry - Zhang, Huize (2019)
The lack of natural resource and energy caused by long-term high-speed economic development at the cost of environmental sustainability as well as the large waste of natural resources caused by public’s weak environmental protection awareness result in resource and environment development dilemma in China. This dissertation examines the board-level influences on the quality of corporate environment sustainable disclosure, focusing on the factors relating to board diversity, board composition, and corporate social responsibility (referred to hereafter CSR) awareness. The board diversity can be further divided by the board independence, board gender diversity, board members’ education level, and board age diversity. The board composition includes the percentage of non-executive directors and board size. The corporate social responsibility awareness refers to whether the corporation issue stand-alone environmental reporting. This dissertation uses quantitative research method, testing the board-level influences via the fixed-effect panel data model. The sample tested in Chinese Information Technology (referred to hereafter IT) industry listed on the Shanghai Stock Exchange for the fiscal year 2013 to the fiscal year 2018. This dissertation discovers that corporate governance can affect the quality and credibility of environmental sustainable disclosure. Therefore we provide suggestions for managers to enhance their environmental sustainable practices and further improve corporate sustainable environmental disclosure quality. In turn, focusing on CSR behaviors can enable firms avoid unnecessary costs resulting from legitimacy risk, finally earning public’s trust and build enterprises’ reputation. For policy-makers, based on the suggestions and conclusions in this dissertation, they can make more detailed regulations at the board-level using corporate governance methods. By standardizing the CSR practices and monitoring the corporate environmentally sustainable disclosure effectively can promote the achievement of social sustainable development goals . The results for this dissertation enrich the research in testing the relationship between corporate governance and sustainable environmental disclosure in Chinese IT industry. Keywords: Environmental sustainable disclosure; Board diversity; Board composition; Board CSR awareness; Chinese IT industry